2012
DOI: 10.2174/1381612811209023170
|View full text |Cite
|
Sign up to set email alerts
|

Implication of microRNAs in the Pathogenesis of MDS

Abstract: MicroRNAs (miRNAs) are significant regulators of human hematopoietic stem cells (HSC), and their deregulation contributes to hematological malignancies. Myelodysplastic syndromes (MDS) represent a spectrum of hematological disorders characterized by dysfunctional HSC, ineffective blood cell production, progressive marrow failure, and an increased risk of developing acute myeloid leukemia (AML). Although miRNAs have been primarily studied in AML, only recently have similar studies been performed on MDS. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 106 publications
0
15
0
1
Order By: Relevance
“…It has been previously published that miR10-a and miR15-a are overexpressed in hematopoietic cells from MDS patients[ 24 ]. In Fig 2 we can observe that these two microRNAs are among the most expressed in MVs from our patients and they were selected to assess if their expression was modified in CD34 + cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously published that miR10-a and miR15-a are overexpressed in hematopoietic cells from MDS patients[ 24 ]. In Fig 2 we can observe that these two microRNAs are among the most expressed in MVs from our patients and they were selected to assess if their expression was modified in CD34 + cells.…”
Section: Resultsmentioning
confidence: 99%
“…MicroRNAs are small non-coding RNAs involved in the regulation of gene expression and have a crucial role in the regulation of hematopoiesis[ 35 ]. MicroRNAs can play a role in the development of some malignant hematopoietic disorders such as MDS[ 24 ]. Evidence that microRNAs deregulation in the microenvironment is involved in MDS pathogenesis comes from the seminal study of Raaijmaikers et al[ 9 ], who demonstrated that, when DICER-1 was deleted in murine osteoprogenitors, these animals developed an MDS similar to the human disease.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 U literaturi se genska ekspresija miRNK dovodi u vezu s dijagnozom, klasifikacijom i progresijom raz ličitih bolesti: B-kroničnom limfocitnom leukemijom (B-KLL), 6 karcinomom pluća, 7 hepatocelularnim karcinomom, 8 akutnom mijeloičnom leukemijom (AML). 9 Istraživanja miRNK u MDS-u relativno su rijetka, većina ih je usmjerena na višestruko profiliranje različitih miRNK, a tek nekoliko na patogenezu i nastanak MDS-a s kojim se u vezu dovode snižene razine genskih ekspresija specifičnih miRNK hsa-miR--146a, hsa-miR-150, let-7e, hsa-miR-23a, hsa-miR--103, hsa miR-126. [10][11][12] Povišenu razinu genske ekspresije miRNK hsa-miR-125b u MDS-u opisali su 2008. godine Bousquet i suradnici.…”
Section: Discussionunclassified
“…12 Not only have these coding gene mutations been linked to disease progression and prognosis in MDSs, [13][14][15][16][17] but dysregulation of noncoding RNAs, such as the microRNAs, have also been implicated as important elements in the pathogenesis and disease evolution of MDSs. [18][19][20][21] Recent research works have revealed that the long noncoding RNAs (lncRNAs), a novel class of versatile noncoding RNAs operationally defined as transcripts longer than 200 nucleotides, play crucial roles in a constellation of biological processes including chromatin modification, regulation of gene expression in various signaling pathways, genomic imprinting, and epigenetic control. [22][23][24][25] Although a myriad of previous publications have established the association between deranged lncRNA expression and carcinogenesis, tumor progression, and metastasis in a wide variety of solid cancers, [26][27][28][29][30][31][32][33] relatively limited data exist so far on how these lncRNAs are involved in normal and malignant hematopoiesis.…”
Section: Introductionmentioning
confidence: 99%